2006
DOI: 10.1007/s00467-006-0065-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum cystatin C in children with congenital solitary kidney

Abstract: The aim of the study was to assess serum cystatin C level in children with a congenital solitary kidney, depending on their age and compensatory overgrowth of the kidney. The study group (I) consisted of 36 children, 3-21 years of age (median 10.8 years), with a congenital solitary kidney and no other urinary defects. The control group (C) contained 36 healthy children, 5-21 years old (median 10.9 years). Nephelometric methods were used to determine serum cystatin C level, the Jaffe method to assess creatinine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Because this problem is widely recognized and underlined in the K/DOQI guidelines (9), we discourage the use of Ccreat to monitor GFR in patients with an SFK. Wasilewska et al determined serum cystatin C levels in 36 children with a congenital SFK and no other urinary tract defects (34). Compared with a healthy control group, they found increased serum cystatin C levels in children with an SFK older than age 12 years, whereas the original Schwartz formula yielded normal results.…”
Section: Discussionmentioning
confidence: 99%
“…Because this problem is widely recognized and underlined in the K/DOQI guidelines (9), we discourage the use of Ccreat to monitor GFR in patients with an SFK. Wasilewska et al determined serum cystatin C levels in 36 children with a congenital SFK and no other urinary tract defects (34). Compared with a healthy control group, they found increased serum cystatin C levels in children with an SFK older than age 12 years, whereas the original Schwartz formula yielded normal results.…”
Section: Discussionmentioning
confidence: 99%
“…Serum cystatin C has been examined in a number of patient populations, including healthy children, 17 renal transplant recipients, 18 and patients with glomerulonephritis or various renal diseases. [19][20][21] In many studies, serum cystatin C-derived GFR was equivalent to radioisotope (125-I iothalamate) determination of GFR and 24-h urine for creatinine clearance, and was superior to serum creatinine for monitoring renal impairment. 22 GFR based on the serum creatinine Schwartz formula showed poor performance across all GFR levels and in each of the Stage I to III CKD groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with those of previous studies in addition to the investigation of serum cystatin C as a marker of GFR in patients with chronic renal disease. [19][20][21] Bacchetta et al evaluated the external validity of several published bedside formulas based on plasma creatinine or serum cystatin C in comparison with the reference method in a French pediatric cross-sectional cohort of 252 patients. 23 Bacchetta et al showed that most of the cystatin C-derived formulas for estimating GFR seem accurate in non-selected pediatric patients and also suggested that the cystatin C-derived formulas can be used reliably when reference methods for measuring the true GFR are not available or when the local adaptation of Schwartz formula has not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…In children with renal dysplasia, González et al (16) studied the progression of chronic renal failure in children with dysplasia kidneys, and found deterioration of renal function was related to albuminuria, eGFR (estimated GFR) at onset of deterioration, hypertension, number of febrile urinary tract infections and puberty. Wasilewska et al (24) did not find a significant difference in blood pressure and urinary protein level between children with congenital solitary kidney and controls, however, serum cystatin C levels in the patients was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with congenital solitary kidney often had a larger kidney than normal (7,24). Hill et al (7) studied renal length in fetuses with solitary kidney, and found that as early as 22 weeks' gestation the lengths of the solitary functioning kidney were increased in 44% of cases assessed by ultrasound.…”
Section: Discussionmentioning
confidence: 99%